Implementasi Metode Weighted Product dan Pembobotan Rank Order Centroid Dalam Pemberian Penghargaan Predikat Kader Terbaik - Feri Setiawan; Lusiyanti Lusiyanti; Dedi Setiawan (STMIK Budi Darma, 2022)
This study discusses the process of awarding the best cadres by utilizing a decision support system using the Weighted Product method and the criteria weighting method using the Rank Order Centroid to obtain the weighting of the criteria systematically with the case studies studied, namely the Leadership of the Commissariat of Muhammadiyah Students, Faculty of Computer Science, University of Muhammadiyah Riau. The procedure carried out in awarding the best cadres by using several alternative data samples and several criteria related to the assessment. The number of alternative data used to be tested in this study were 10 samples of alternative data and 5 assessment criteria. The criteria used are Activeness (K1), Level of Training (K2), Grade Point Average (K3), Leadership (K4), and Teamwork (K5). The results obtained after testing are A6 as the best alternative with the final value obtained of 0.3398 and declared as the best cadre. The Weighted Product method and assisted by the Rank Order Centroid weighting method are able to make decisions for awarding the best cadres to the Commissariat Leaders of the Muhammadiyah Student Association, Faculty of Computer Science, University of Muhammadiyah Riau.